Detection of bladder cancer with aberrantly fucosylated ITGA3 - Islam Md Khirul; Syed Parvez; Dhondt Bert; Gidwani Kamlesh; Pettersson Kim; Lamminmäki Urpo; Leivo Janne (Academic Press Inc Elsevier Science, 2022)
We describe a simple, non-invasive assay to identify fucosylated-glycoisoform of integrin alpha-3 (ITGA3) directly from unprocessed urine. ITGA3 was detected directly from the urine of bladder cancer (BlCa) (n = 13) and benign prostatic hyperplasia (BPH) (n = 9) patients with the use of lectins coated on europium-dopednanoparticles (Eu3+-NPs). Lectin Ulex europaeus agglutinin-I (UEA) showed enhanced binding with BlCaderived ITGA3. The evaluation with individual samples showed that a glycovariant ITGA3-UEA assay could significantly discriminate BlCa from BPH patients (p = 0.007). The detection of aberrantly fucosylated-isoform of ITGA3 from urine can be used to distinguish BlCa from age-matched benign controls in a simple sandwich assay.